0570 Does CBT-I Dose effect Sleep Duration and Fatigue in Breast and Prostate Cancer Patients?. (25th May 2022) - Muench, Alexandria; Posner, Donn; Seewald, Mark; Upton, Caitlyn; Boyle, Julia; Reddy, Varudhini; Thompson, Michelle; Vargas, Ivan; Perlis, Michael
Abstract: Introduction: Cancer-related fatigue (CRF) is highly prevalent during acute illness and survivorship, with almost 100% of cancer patients experiencing some level of CRF. While CRF commonly co-occurs with sleep disturbance during and/or after cancer treatment, CRF is defined as occurring independent of sleep considerations. The present analysis is based on an ongoing pilot study where CBT-I dose (4 & 8 [Low] vs 10 & 12 [High] sessions) is being assessed for whether improved sleep continuity and/or increased TST can improve CRF in subjects diagnosed with breast and prostate cancer. Methods: This interim analyses includes seven adult subjects (6 females, mean age=57.1 yrs.; n=3 [Low dose], n=4 [High dose]). CBT-I was provided by a master CBT-I therapist via video conferencing (telehealth CBT-I). Subjects were asked to complete sleep diaries, and weekly measures of fatigue (FACIT) and insomnia severity (ISI) questionnaires. Results: Subjects in the low dose group exhibited a 9% improvement and subjects in the high dose group had a 21% improvement on the FACIT. This corresponded to a 28% improvement on the ISI (low group) and a 68% improvement on the ISI (high group). With respect to TWT, subjects in the low dose group decreased their wake time by 36% and those in the high dose group decreased their wake time by 43%. Finally, TST decreased by 7% in the low dose group but increased by 12% in the high dose group. Conclusion: Preliminary results indicate that a higher CBT-I dose may significantly decrease fatigue, stabilize sleep schedules, and improve sleep continuity in patients with CRF, where the high dose group showed more than double the improvement on the FACIT and ISI (as compared to the low dose group). Not surprisingly, TWT was roughly comparable between the groups while TST was more substantially impacted by high dose CBT-I. This study is ongoing. Support (If Any): Support: 5T32HL00795320;K24AG055602